Transcultural translation-adaptation to Spanish of the Infants’ Dermatitis Quality of Life questionnaire for children under four years with atopic dermatitis - Carmen Alexandra Maza-De Franco; Martha Alejandra Morales-Sánchez; María Enriqueta Morales-Barrera (Revista Alergia México, 2016)
Background: Atopic dermatitis is observed in up to 20% of children, hence the importance of tools to support its evaluation.